Examination of aryl hydrocarbon receptor (AhR), estrogenic and anti-androgenic activities, and levels of polyaromatic compounds (PACs) in tire granulates using in vitro bioassays and chemical analysis. (July 2022) - Eriksson, Ulrika; Titaley, Ivan A.; Engwall, Magnus; Larsson, Maria
Abstract: Tire granulates recovered from end-of-life tires contain a complex mixture of chemicals, amongst them polyaromatic compounds (PACs), of which many are recognized to be toxic and persistent in the environment. Only a few of these PACs are regularly monitored. In this study a combined approach of chemical analysis and a battery of CALUX® in vitro bioassays was used to determine PAC concentrations and estrogenic, (anti)-androgenic and aryl hydrocarbon receptor (AhR) activities in tire granulates. Tire granulates from a recycling company was analyzed for PAHs, alkyl-PAHs, oxy-PAHs and heterocyclic PACs (NSO-PACs), in total 85 PACs. The concentrations of PACs were between 42 and 144 mg/kg, with major contribution from PAHs (74–88%) followed by alkyl-PAHs (6.6–20%) and NSO-PACs (1.8–7.0%). The sum of eight priority PAHs were between 2.3 and 8.6 mg/kg, contributing with 4.7–8.2% of ∑PACs. Bioassay analysis showed presence of AhR agonists, estrogen receptor (ERα) agonists, and androgen receptor (AR) antagonists in the tire granulate samples. Only 0.8–2.4% of AhR-mediated activities could be explained by the chemical analysis. Benzo[k+j]fluoranthenes, benzo[b]fluoranthene, indeno[1, 2, 3-cd]pyrene, 2-methylchrysene, and 3-methylchrysene were the major contributors to the AhR-mediated activities. The high contribution (98–99%) of unknown bioactive compounds to the bioassay effects in this study raises concerns and urges for further investigations of toxicants identification and source apportionment. Graphical abstract: Image 1 Highlights: A total number of 54 PACs were found in the tire granulates. Only 0.8–2.4% of the AhR-mediated activity could be explained by targeted PACs. Methylchrysene were amongst the major contributors to the AhR-mediated response. High AhR-, ERα-, and anti-AR activity were measured in all tire granulates.